Quantification of gravity-induced skin strain across the breast surface. (December 2017) - Sanchez, Amy; Mills, Chris; Haake, Steve; Norris, Michelle; Scurr, Joanna
Abstract: Background: Quantification of the magnitude of skin strain in different regions of the breast may help to estimate possible gravity-induced damage whilst also being able to inform the selection of incision locations during breast surgery. The aim of this study was to quantify static skin strain over the breast surface and to estimate the risk of skin damage caused by gravitational loading. Methods: Fourteen participants had 21 markers applied to their torso and left breast. The non-gravity breast position was estimated as the mid-point of the breast positions in water and soybean oil (higher and lower density than breast respectively). The static gravity-loaded breast position was also measured. Skin strain was calculated as the percentage extension between adjacent breast markers in the gravity and non-gravity loaded conditions. Findings: Gravity induced breast deformation caused peak strains ranging from 14 to 75% across participants, with potentially damaging skin strain (> 60%) in one participant and skin strains above 30% (skin resistance zone) in a further four participants. These peak strain values all occurred in the longitudinal direction in the upper region of the breast skin. In the latitudinal direction, smaller-breasted participants experienced greater strain on the outer (lateral) breast regions and less strain on the inner (medial) breast regions, a trend which was reversed in the larger breasted participants (above size 34D). Interpretation: To reduce tension on surgical incisions it is suggested that preference should be given to medial latitudinal locations for smaller breasted women and lateral latitudinal locations for larger breasted women. Highlights: Quantification of breast skin strain to inform incision locations during surgery Up to 75% skin strain in the longitudinal direction in upper region of breast Smaller-breasted participants experienced greater strain on lateral breast regions Larger-breasted participants experienced greater strain on medial breast regions